Analisis Self Efficacy dengan Kualitas Hidup Pasien Odha di Komunitas X Palembang - Bangun Dwi Hardika; Maria Tarisia Rini; Vausta Nurjanah (Jurnal Akademika Baiturrahim Jambi, 2023)
Human Immunodeficiency Virus (HIV) is a virus that can damage the human immune system and can only multiply in living cells and is found in body fluids, especially in semen, vaginal fluids, and blood. HIV patients usually have difficulty adapting to themselves and accepting their current conditions, coupled with the treatment from the community towards them so that it will affect the quality of life of odha. A person's adaptation is closely related to self-efficacy and quality of life. The research objective was to analyze the relationship between self-efficacy and the quality of life of people with HIV in Palembang. This study is an analytical survey with a cross-sectional design. The research population is people living with HIV in Community X Palembang. The sampling technique was purposive sampling according to the inclusion and exclusion criteria. Data were analyzed univariately and bivariately with the tau control test. The results showed that there was no relationship between self-efficacy and the quality of life of PLHIV with a p value of 0.088. Respondents are expected to maintain self-efficacy because the relationship is positive, which means that if self-efficacy is good it will improve the quality of life.